Açık ya da kapalı büyük ameliyatların cerrahi dumanı hastanın karbonsihemoglobin, methemoglobin ve bazı kan gazlarını olumsuz etkiler mi? - BİÇER, Elif (My University, 2020)
Surgical smoke appears in the majority of closed or open surgeries.Carcinogens in the smoke cause non-negligible risks. The aim of this study is to investigate the effect of the surgical smoke caused by the surgical instruments on levels of patients` blood gas, carboxyhemoglobin, and methemoglobin. The descriptive study was carried out in Gaziosmanpaşa Taksim Training and Research Hospital between April 2019 and October 2019 after the approval of the ethics committee and institution. The study was conducted in 87 volunteer patients who were scheduled for open and closed surgery. The data was collected with laboratory reports and 'the Patient Identification Information Form' which contained 20 questions. The normality distribution of the data was analyzed in IBM SPSS 22.0 program and proper comparison tests were selected. Differences were considered statistically significant at p < 0.05 level. The mean age of the participants was 56.45 ± 16.30 and the body mass index was 25.22 ± 3.24. 57.5% (n = 50) of the participants were smokers, 63.2% (n = 55) did not have any chronic diseases, 21.8% (n = 19) had cardiovascular diseases, 15% (n = 13) had a metabolic disease. There was the only airflow in all rooms where the participants underwent surgery. The mean duration of surgery was 3.78 ± 1.59 hours. In open surgical procedures (n = 56), the effects of surgical smoke on blood gas were less (p <0.05) than laparoscopic surgical procedures (n= 31). In terms of surgical smoke production, monopolar (71.3%) and bipolar (48.3%) inserts of electrocautery were more than laser and ultrasound scissors (p <0.05). The method used to remove surgical smoke was a 46% aspiration probe. Aspiration probes indicated positive effects on blood gases and carboxyhemoglobin (p <0.05). It was found that the mean bleeding of patients was 412,18±530,44 cc during operations. It was observed that significant changes in arterial PaCO2, PaO2, MetHb, COHb, pH levels compared to preoperative values (p=0.035; p=0.001; p=0.052; p=0.640; p=0.034). In the present study, surgical cutters used in the majority of patients had surgical smoke production. Postoperative arterial PaCO2, PaO2, MetHb, COHb, changes in pH values compared to preoperative values of the patients indicate that there is not an effective ventilation system and a successful technique to remove smoke from tissues. In this study, surgical instruments used in the majority of patients cause surgical smoke production. Postoperative changes in arterial PaCO2, PaO2, MetHb, COHb and pH levels compared to the preoperative levels of the patients indicate that there is no effective ventilation system and a successful technique to remove smoke from the tissues.
Cerrahi duman açık ve kapalı cerrahi girişimlerin çok büyük bir çoğunluğunda ortaya çıkmaktadır. Duman içerisindeki karsinojenler ihmal edilemez bir risk durumu oluşturmaktadır. Bu araştırma, açık ya da kapalı büyük ameliyatlarda kullanılan cihazların oluşturduğu cerrahi dumanın hastanın kan gazı, karboksihemoglobin ve methemoglobin değerleri üzerindeki etkisini incelemek amacıyla yapıldı. Tanımlayıcı nitelikteki araştırma, etik kurul ve kurum izinleri tamamlandıktan sonra Nisan 2019 – Ekim 2019 tarihleri arasında, Gaziosmanpaşa Taksim Eğitim ve Araştırma Hastanesinde gerçekleştirildi. Araştırma 87 gönüllü açık ve kapalı ameliyat planlanan hastada yapıldı. Veriler 20 sorudan oluşan 'Hasta Tanıtıcı Bilgi Formu' ve laboratuvar sonuç raporları ile toplandı. Verilerin IBM SPSS 22.0 programında normallik dağılımı incelenerek uygun karşılaştırma testleri seçildi. İstatistiksel anlamlılık değeri p<0.05 kabul edildi. Araştırmadaki katılımcıların ortalama yaşı 56,45±16,30, beden kitle indeksi 25,22±3,24 idi. Katılımcıların %57,5'i (n=50) sigara kullanıyordu, %63,2'sinde (n=55) herhangi bir kronik hastalık yoktu, %21,8'inde (n=19) kalp ve damar hastalıkları, %15'inde (n=13) ise metabolik bir hastalık vardı. Katılımcıların ameliyat edildiği tüm odalarda sadece laminar hava akımı vardı. Hastaların ortalama ameliyatta kalma süresi 3,78±1,59 saatti. Açık cerrahi girişimlerde (n=56), laparoskopik cerrahi girişimlere (n=31) göre cerrahi dumanın kangazı etkileri daha azdı (p<0.05). Cerrahi duman üretimine bakıldığında elektrokoterin monopolar (%71,3) ve bipolar (%48.3) kesici uçları; laser ve ultrasound kesicilerden daha fazlaydı (p<0.05). Cerrahi dumanı uzaklaştırmak için kullanılan yöntem %46 aspirasyon çubukları idi. Aspirasyon çubukları kangazları ve karboksihemoblobin üzerinde olumlu etki gösterdi (p<0.05). Ameliyat sırasında hastaların ortalama 412,18±530,44 cc kanaması olduğu belirlendi. Ameliyat öncesine göre ameliyat sonuna doğru arteriyel PaCO2, PaO2, MetHb, COHb, pH değerlerinde önemli değişiklikler görüldü (p=0.035; p=0.001; p=0.052; p=0.640; p=0.034). Sunulan araştırmada hastaların çoğunluğuna kullanılan cerrahi kesicilerin cerrahi duman üretimi vardı. Hastaların ameliyat öncesine göre ameliyat sonu arteriyel PaCO2, PaO2, MetHb, COHb, pH değerlerindeki değişimler, etkin bir havalandırma sistemi ve dokulardan dumanı uzaklaştırabilecek başarılı bir teknik olmadığını göstermektedir.
Keywords: Hemşirelik = Nursing; Hemşirelik Anabilim Dalı; Department of Nursing; Sağlık Bilimleri Enstitüsü; Ameliyathane hemşireliği = Operating room nursing; Surgical smoke; carboxyhemoglobin; Methemoglobin